2021
DOI: 10.1155/2021/6677132
|View full text |Cite
|
Sign up to set email alerts
|

A Markov Chain Position Prediction Model Based on Multidimensional Correction

Abstract: User location prediction in location-based social networks can predict the density of people flow well in terms of intelligent transportation, which can make corresponding adjustments in time to make traffic smooth, reduce fuel consumption, reduce greenhouse gas emissions, and help build a green cycle low-carbon transportation green system. This paper proposes a Markov chain position prediction model based on multidimensional correction (MDC-MCM). Firstly, extract corresponding information from the user’s hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…rough this research, it was found that the pedestrian speed is under the influence of various parameters, and measuring all the variations is complex and is suggested that in future studies, the researchers find other effective parameters for the pedestrian moving speed. Moreover, machine learning methods can be incorporated into the proposed approaches [61][62][63]. Deep learning models can also obtain more accurate results [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…rough this research, it was found that the pedestrian speed is under the influence of various parameters, and measuring all the variations is complex and is suggested that in future studies, the researchers find other effective parameters for the pedestrian moving speed. Moreover, machine learning methods can be incorporated into the proposed approaches [61][62][63]. Deep learning models can also obtain more accurate results [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Sharifi et al [ 33 ] studied the impact of artificial intelligence and digital style on the industry and energy following COVID-19. According to Chen et al [ 34 ], a Markov chain position predictions model based on multilevel correction was presented. This approach is also helpful in determining the correlation between the variables in the COVID-19 dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e family of numerical methods includes finite difference [21], finite element [22], the finite volume [23][24][25], and some related extensions which gives numerical solutions of the problems. e class of methods including Adomian decomposition, differential transform [11], variation iteration [10], Homotopy perturbation, Homotopy analysis etc., which give solutions in terms of series contains different drawbacks including calculation of polynomials, multipliers, perturbing, and sometimes diverged for the problems contains the higher nonlinearity factor [19,20,[24][25][26]. In the spectral methods, convergence insurance and accuracy level achievement is really high but it got some issues in terms of time and cost.…”
Section: Introductionmentioning
confidence: 99%